ANALYSIS OF PRODUCT INNOVATION, PRODUCT QUALITY AND CUSTOMER SATISFACTION ON COMPETITIVE ADVANTAGE (SURVEY OF MSMEs IN SOEDIRMAN STREET FOOD SUKABUMI) - Disa Siti Nurjanah; Dicky Jhoansyah; Sopyan Saori (Universitas KH. Abdul Chalim Mojokerto, 2025)
Micro, Small and Medium Enterprises (MSMEs) are types of productive businesses owned by individuals or business entities that meet the criteria as micro businesses. One of them is Soedirman Street Food Sukabumi which is a gathering place for micro, small and medium enterprises (MSMEs) in the food and beverage sector, which has problems in competitive advantage as well as product innovation, product quality and customer satisfaction. The purpose of this study was to determine how product innovation, product quality and customer satisfaction affect competitive advantage. The population in this study were MSMEs at Soedirman Street Food Sukabumi. The sample used amounted to 34 respondents and was obtained through saturated sampling technique. The method used is a quantitative method with an associative descriptive approach. The results of the f test statistics (simultaneously) there is a simultaneous and significant influence of the variables of product innovation, product quality and customer satisfaction on competitive advantage. Based on the statistical results of the t test (partial test) product innovation has a negative and insignificant effect on competitive advantage. While product quality and customer satisfaction have a positive and significant effect on competitive advantage.